Detoxification of the Fumonisin Mycotoxins in Maize: An Enzymatic Approach - Alberts, Johanna (Toxins (Basel), 2019)
Enzymatic detoxification has become a promising approach for control of mycotoxins postharvest in grains through modification of chemical structures determining their toxicity. In the present study fumonisin esterase FumD (EC 3.1.1.87) (FUMzyme(®); BIOMIN, Tulln, Austria), hydrolysing fumonisin (FB) mycotoxins by de-esterification, was utilised to develop an enzymatic reduction method in a maize kernel enzyme incubation mixture. Efficacy of the FumD FB reduction method in “low” and “high” FB contaminated home-grown maize was compared by monitoring FB(1) hydrolysis to the hydrolysed FB(1) (HFB(1)) product utilising a validated LC-MS/MS analytical method. The method was further evaluated in terms of enzyme activity and treatment duration by assessing enzyme kinetic parameters and the relative distribution of HFB(1) between maize kernels and the residual aqueous environment. FumD treatments resulted in significant reduction (≥80%) in “low” (≥1000 U/L, p < 0.05) and “high” (100 U/L, p < 0.05; ≥1000 U/L, p < 0.0001) FB contaminated maize after 1 h respectively, with an approximate 1:1 µmol conversion ratio of FB(1) into the formation of HFB(1). Enzyme kinetic parameters indicated that, depending on the activity of FumD utilised, a significantly (p < 0.05) higher FB(1) conversion rate was noticed in “high” FB contaminated maize. The FumD FB reduction method in maize could find application in commercial maize-based practices as well as in communities utilising home-grown maize as a main dietary staple and known to be exposed above the tolerable daily intake levels.